Highly Enantioselective Synthesis of Chiral Tetrahydroquinolines and Tetrahydroisoquinolines by Ruthenium‐Catalyzed Asymmetric Hydrogenation in Ionic Liquid. Issue 18 (6th December 2013) - Ding, Zi‐Yuan; Wang, Tianli; He, Yan‐Mei; Chen, Fei; Zhou, Hai‐Feng; Fan, Qing‐Hua; Guo, Qingxiang; Chan, Albert S. C.
Abstract Asymmetric hydrogenation reactions of quinolines and 3, 4‐dihydroisoquinolines using the chiral cationic ruthenium complex Ru(TsDPEN) [TsDPEN=N‐(p‐toluenesulfonyl)‐1, 2‐diphenylethylenediamine] as catalyst in neat imidazolium ionic liquids have been investigated. The catalytic performance was influenced by the anion of the ionic liquids for both substrate classes. A range of 2‐alkyl‐substituted 1, 2, 3, 4‐tetrahydroquinolines and 1‐alkyl‐substituted 1, 2, 3, 4‐tetrahydroisoquinolines was obtained in high yields with up to >99% ee. Interestingly, the hydrogenation of quinoline derivatives bearing a carbonyl group was selective for the CN (quinoline) over the CO (ketone) bonds, while such a unique chemoselectivity was not observed in methanol. Furthermore, the ruthenium catalysts could be easily recycled at least 5 times in the asymmetric hydrogenation of 3, 4‐dihydroisoquinoline by solvent extraction. To further facilitate the recovery of catalyst and reduce the use of organic solvent, a thin film of ionic liquid containing Ru(TsDPEN) was supported on silica gels. This supported ionic liquid‐phase catalyst was effective in the asymmetric hydrogenation of quinoline, and could be recycled at least 6 times by simple filtration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>